Longitudinal associations between adolescents' trajectory membership of depressive symptoms and suicidality in young adulthood: a 10-year cohort of Chinese Wenchuan earthquake survivors. (2020) - Chen, Xiao-Yan; Zhou, Ya; Shi, Xuliang; Ma, Zijuan; Fan, Fang
Abstract: Aims: Previous studies regarding associations between depressive symptoms and suicidality (suicidal ideation, plans and attempts) have usually employed a variable-centred approach, without considering the individual variance in time-varying changes of depressive symptoms. Through 10-year follow-up of a large cohort of Chinese adolescents exposed to the 2008 Wenchuan earthquake, this study examined whether individual variance in depressive symptoms during the early phases post-earthquake could generate different suicidality outcomes in young adulthood. Methods: A total of 1357 Chinese adolescents exposed to the Wenchuan earthquake were surveyed on depressive symptoms and other variables at 6, 18 and 30 months post-earthquake. In total, 799 participants responded to the 10-year follow-up and completed an online survey covering suicidality and other variables. The analytic sample was 744 participants who had valid data on depressive symptoms and suicidality. Data were analysed using logistic regressions. Results: Prevalence estimates of past-year suicidal ideation, suicide plans and suicide attempts measured at 10 years post-earthquake were found to be 10.8%, 7.3% and 3.0%, respectively. Five trajectories of depressive symptoms were classified: resistance (54.4%), chronicity (13.3%), recovery (10.4%), delayed dysfunction (12.0%) and relapsing/remitting (10.0%). After controlling for covariates, whole-sample regressions revealed only the relapsing/remitting depressive trajectory remained significantly predictive of suicidality. Moreover, males not females in the chronic group were more likely to have suicide plans. Conclusions: The findings highlight the importance of detecting disaster survivors with different trajectories of mental status and providing with them individualised and effective mental health services, to decrease their risk of suicidality in the future.